The impacts of human activity on mammals in a community forest near the Dja Biosphere Reserve in Cameroon - Tudge, SJ; Brittain, S; Kentatchime, F; Kamogne Tagne, CT; Rowcliffe, JM (Cambridge University Press, 2022)
Human activity in African tropical rainforests continues to threaten wild mammals. Many rural communities are dependent on hunting, yet there is a widespread lack of baseline data on ecology and the sustainability of hunting. We investigated the impacts of human activity on mammal species composition and distributions within a community forest surrounding a village in the buffer zone of the Dja Biosphere Reserve in south-east Cameroon. We conducted a camera-trap survey in August–November 2017 and detected 24 mammal species, including Critically Endangered western lowland gorilla Gorilla gorilla gorilla, Endangered central African chimpanzee Pan troglodytes troglodytes and Endangered tree pangolin Phataginus tricuspis. We used occupancy analysis to explore relationships between indicators of human activity (distance to a road and the Reserve), habitat quality (distance to the river and tree cover) and the distributions of species. We found that the local distribution of threatened mammals was not apparently limited by human activity, and proximity to the road did not negatively influence occupancy for any species. However, most of the Reserve's large species were not detected, including the African forest elephant Loxodonta cyclotis and the largest ungulates, and the occupancy of two species commonly hunted for wild meat was positively correlated with distance from the village, indicating hunting may be unsustainable. Our results show that the community forest provides habitat for threatened species outside the Reserve and in close proximity to people. However, effective conservation management will require continued monitoring and research to determine whether current rates of hunting are sustainable.